Dissecting the shared genetic architecture of bipolar disorder, major depressive disorder, and attention-deficit hyperactivity disorder - Christopher Lawrence; Thomas Folkmann Hansen (PLoS ONE, 2026)
Major depressive disorder (MDD), bipolar disorder (BPD), and attention-deficit hyperactivity disorder (ADHD) are prevalent, highly heritable psychiatric disorders with significant degrees of genetic overlap. Using open-sourced summary statistics from the Psychiatric Genomics Consortium and 1000 Genomes European reference panel, we fit a latent factor model (F1) capturing the shared genetic liability across MDD, BPD, and ADHD. Multivariate GWAS identified 350 linkage disequilibrium-independent loci, 105 of which have not been previously reported by the contributing univariate GWASs. Univariate, bivariate, and trivariate mixture models elucidated both shared and trait-specific polygenicity across the disorders. Gene-level analysis with Hi-C coupled MAGMA identified a total of 2936 novel dopaminergic associations across the constituent disorders that went undetected in univariate analyses. Among the top genes associated with F1, protein tyrosine phosphatase receptor type D emerged as a promising candidate. Cell typing and brain tissue enrichment for F1 further implicated the cerebellum and cholinergic neurons. These findings demonstrate how multivariate approaches can elucidate shared biological mechanisms, providing new etiological insights into individual disorders and implicating therapeutic targets for the treatment of psychiatric comorbidity.